1921 N.M. Laws 201-02 - (:unkn) unknown (My University, 1921)
Ch. 113, §§ 1-4: Prohibited the use, possession, or control of any shotgun or rifle by noncitizen; violators subject to fine, imprisonment, and confiscation and resale of shotgun or rifle
Keywords: POSSESSION - DANGEROUS PERSONS